The Influence Of The Arabic Language On Legal Terminology: The Term Hisbah As A Case Study/ تأثير اللغة العربية في المصطلحات الشرعية: مصطلح الحسبة نموذجاً - Alabri, Khalid Hassan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research explores one of the fundamental principles of terminology and the extent of the Arabic language’s influence on Islamic legal terms. It focuses on Hisbah, which has become widely associated with